Relevance of the Watson-Jones anterolateral approach in the management of Pipkin type II fracture-dislocation: a case report and literature review - Nazim Sifi; Ryad Bouguenna (Journal of Trauma and Injury)
Femoral head fractures with associated hip dislocations substantially impact the functional prognosis of the hip joint and present a surgical challenge. The surgeon must select a safe approach that enables osteosynthesis of the fracture while also preserving the vascularization of the femoral head. The optimal surgical approach for these injuries remains a topic of debate. A 44-year-old woman was involved in a road traffic accident, which resulted in a posterior iliac dislocation of the hip associated with a Pipkin type II fracture of the femoral head. Given the size of the detached fragment and the risk of incarceration preventing reduction, we opted against attempting external orthopedic reduction maneuvers. Instead, we chose to perform open reduction and internal fixation using the Watson-Jones anterolateral approach. This involved navigating between the retracted tensor fascia lata muscle, positioned medially, and the gluteus medius and minimus muscles, situated laterally. During radiological and clinical follow-up visits extending to postoperative month 15, the patient showed no signs of avascular necrosis of the femoral head, progression toward coxarthrosis, or heterotopic ossification. The Watson-Jones anterolateral approach is a straightforward intermuscular and internervous surgical procedure. This method provides excellent exposure of the femoral head, preserves its primary vascularization, allows for anterior dislocation, and facilitates the anatomical reduction and fixation of the fracture.